The Study of Nurses Knowledge and Performance Quality of Qazvin Hospitals about the Process of Blood Transfusion - Nemati, Fatemeh; Maali, Amirhosein; Ahmadi, Mohammad Hossein; Poorkarim, Hoda; Rahmani, Hanieh; Tabatabaei, Zahra Sadat; Azad, Mehdi (Advances in Nursing & Midwifery, 2019)
Introduction: Supplying blood and blood products, maintenance, transfer and injection of each component have its own specific process. Therefore, those responsible must at least have the awareness that relates to the transfusion medicine. The safety and effectiveness of blood transfusion depend on the knowledge and skills of nurses, who have taken the responsibility. The aim of this study is to assess the educational needs of nurses in the field of blood transfusion that leads to creating a good medical process for nurses in clinical departments of hospitals. Methods: In this cross-sectional study, 124 nurses who participated in, were selected through random sampling in Qazvin hospitals in 1396. A questionnaire including 25 questions was used to evaluate the knowledge and performance of their awareness of different aspects of blood medicine, including maintenance, transferring, injection and post blood transfusion reactions. The scores of knowledge and performance encoded in three levels: low, medium, and good. Data analysis and correlation of variance were performed by using the software SPSS version 20. Results: Research results showed that most of the subjects are in the age group 20-30 years (68.7%) and females (93%) and have a bachelor’s degree in nursing (95.6%). Results showed that the mean score of knowledge was 9.58±2.13, and score range was 9 (between 3 to 12). The mean score of performance was 38.96±2.17, with range 10 (scores were between 30 to 40). The analysis of variance used to examine the relationship. The results suggested that there was a significant relationship between performance and knowledge of subjects (P<0.05). Conclusions: According to this study, nurse’s knowledge level and awareness of blood transfusion are the media. Therefore, training, managers controlling and supervision programs seem to be necessary due to the great importance of the blood transfusion process and threaten the safety of patients. So, we recommend that this issue must be seriously included in academic courses and retraining in the field of blood transfusion, according to the latest available standards at the time of the nurse’s employment.